Estudo da produtividade em micro e pequenas empresas atuantes na terceirização e fabricação de confecção de vestuário - Nascimento, Hilton Freire do (2010)
The theme of productivity has been increasingly discussed in the light of the great difficulty that companies have to improve it continuously. In this sense, we observed that achieve the highest levels of productivity has been a particular problem of the industries that operate in the business of garment making. In this activity, economic productivity can occur due to various factors of production as well as due to administrative factors related to the productivity of direct labor, productivity, financial and productivity of raw materials. As a result, delimited to the theme of this dissertation based on the productivity of companies in the sourcing and manufacture of clothing, in order to suggest improvements in the productivity of the surveyed companies. For this purpose, was held in the city of Caruaru, Pernambuco an exploratory and descriptive research, combining elements predominantly qualitative with quantitative elements, where the variables and indicators were extracted from the generic model (generic because it does not specify any economic activity) of Thiry-Cherques (1991 ), and indicators of measures by mathematical equations of Smith (1993) that defines productivity through a relationship between outputs and inputs of productive resources. Thus, using the variables (economic forces, behavioral, organizational and institutional justify different levels of productivity in business) model contained in the Thiry-Cherques was possible to establish indicators of productivity for manufacturing companies studied, which served as a parameter to suggest improvements in productivity, contributing to the treatment process and analysis of data searched through multicase study. The data was collected by questionnaire to the general manager / owners of the companies studied, and was performed on-site observation. The results indicated the need for management training, the outsourcer company predation in relation to outsourcing and productivity that can be improved in all aspects studied. In the case of productivity direct labor of companies, it was found that it is only 0.62%. Regarding the financial productivity of companies, it was found that it is negative, ie, is -5%. Regarding the productivity of the main raw material (jeans fabric), the productivity of companies is only 65%. With the results, it was possible to suggest improvements in the productivity of businesses of order qualitative and quantitative. The proposed improvements were made mainly in relation to the management body, the form of outsourcing and the three main factors of production established by this dissertation, ie, productivity of labor, financial productivity and productivity of the main raw material. However, it is understood that the main purpose of improvement made refers to the union of outsourcing companies in a single industrial plant and a new model of outsourcing.